2007
DOI: 10.1159/000099066
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Physician’s Attitudes and Practices toward Lipid-Lowering Management Strategies

Abstract: Background: The purpose of the present study was to examine physician’s attitudes and practices toward the use of different lipid-lowering management strategies in patients at increased risk for coronary heart disease (CHD). Aims/Methods: An internet-based questionnaire was completed by 78 general internists and family practitioners (mean age = 49 years; 80% male) affiliated with a large primary care health delivery system in Connecticut. Questions were asked about physician knowledge and use of current nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…On the other hand, a US study reported that primary care physicians had a very high level of awareness (>90%) and were very knowledgeable about managing dyslipidaemia 11. However, another US study involving primary care physicians reported that just one third of them actually adhered to the recommendations of the guideline on lipid management 1.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a US study reported that primary care physicians had a very high level of awareness (>90%) and were very knowledgeable about managing dyslipidaemia 11. However, another US study involving primary care physicians reported that just one third of them actually adhered to the recommendations of the guideline on lipid management 1.…”
Section: Introductionmentioning
confidence: 99%